Self-powered photodetector - Kumar H.; Jit S. (My University, 2025)
The simplest form of the photodetectors is a p-n junction device operated under reverse bias condition. Thus, requirement of a power supply source is essential for the operation of photodetectors. Self-powered photodetectors are a class of devices which requires no external power supply for their operation. Such type of photodetectors may play crucial roles in the Internet of Things (IoTs) and optical sensor networks. Therefore, the present chapter is dedicated to present some recent developments in II-VI group semiconductor-based self-powered photodetectors. Different types of photodetector structures with their working principles have been discussed. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.